Pharaceutical attention to the hypertensive patient (Research, Society and Development, 2021)
Hypertension is a clinical condition with characteristics related to the sustained elevation of blood pressure levels greater than or equal to 140/90 mmHg. It is a disease that stands out in the current national epidemiological scenario because of its high incidence and prevalence. The objectives of this study are to expand, through a literature review, the knowledge about pharmaceutical assistance to patients diagnosed with arterial hypertension, to analyze the factors related to the use of antihypertensive drugs, and to demonstrate the importance of the pharmaceutical professional in the control of arterial hypertension, as well as in the adequate use of the drugs prescribed to the patient. In Brazil, this disease contributes directly or indirectly to deaths from cardiovascular disease and affects the population of adult individuals, the elderly being the great majority of this group. The diagnosis of hypertension is basically established by the finding of permanently elevated blood pressure levels above normal limits, when blood pressure is determined through appropriate methods and conditions. Currently, faced with the pandemic of COVID-19 one of the most frequent comorbidities in patients who died was arterial hypertension. The pharmaceutical activity is primordial in the attention to the hypertensive patient and is recognized as a professional activity able to capture, conduct, improve, access and promote all the benefits of pharmacotherapy.